Clean Water Treatment Based on Household Scale Filtration System for Mountain Community (Nusantara Science and Technology Proceedings, 2021)
Clean water treatment is an important thing in meeting the need for water that is suitable for consumption. So far, some people in Indonesia, especially people who live in mountainous geographical conditions, find it difficult to obtain clean water for their daily needs. The hilly geographical conditions make it difficult to drill water, so the community depends on mountain water sources that are channeled through pipes. However, cloudy water conditions and unstable discharge are problems that must be addressed immediately. Because the use of cloudy water for cooking and drinking can cause health problems. Therefore, in solving these problems, a clean water treatment technology based on a filtration system was designed. This filtration system uses a combination of up-flow (flow direction from bottom to top) and downflow (flow direction from top to bottom). In addition to easily available materials and simple design, this technology is also inexpensive. Based on the results obtained water with clear quality and suitable for consumption so that it can be used for daily needs.